Systems thinking for Aboriginal Health: Understanding the value and acceptability of group model building approaches. (September 2021) - Browne, Jennifer; Walker, Troy; Brown, Andrew; Sherriff, Simone; Christidis, Rebecca; Egan, Mikaela; Versace, Vincent; Allender, Steven; Backholer, Kathryn
Abstract: Systems thinking is increasingly applied to understand and address systemic drivers of complex health problems. In Australia, group model building, a participatory method from systems science, has been applied in various locations to engage communities in systems-based health promotion projects. To date there is limited evidence regarding GMB use with Australian Aboriginal communities. This study aimed to determine the value and acceptability of group model building (GMB) as a methodological approach in research with Aboriginal communities and identify any adaptations required to optimise its utility. Semi-structured interviews were undertaken with 18 Aboriginal health and university staff who had prior experience with a GMB research project. Interview transcripts were inductively analysed using thematic analysis and key themes were organised using an Indigenous research framework. Participants reported that GMB methods generally aligned well with Aboriginal ways of knowing, being, and doing. Participants valued the holistic, visual and collaborative nature of the method and its emphasis on sharing stories and collective decision-making. Group model building was viewed as a useful tool for identifying Aboriginal-led actions to address priority issues and advancing self-determination. Our findings suggest that by bringing together Aboriginal and non-Aboriginal knowledge, GMB is a promising tool, which Aboriginal communities could utilise to explore and address complex problems in a manner that is consistent with their worldviews. In adapting group model building methods, non-Aboriginal researchers should aspire to move beyond co-design processes and enable Aboriginal health research to be entirely led by Aboriginal people. Highlights: Group model building is a promising method for research with Aboriginal communities that is generally consistent with Aboriginal worldviews. Group Model Building may be a useful tool for identifying actions to address priority issues and advancing Aboriginal self-determination. Capacity building is required so that Group Model Building workshops, and ideally entire research projects, can be led by Aboriginal people.